Cardiac Monitoring and Heart Failure in Advanced Breast Cancer Patients Treated With Trastuzumab in Ontario, Canada - Rushton, Moira; Kappel, Coralea; Lima, Isac; Tuna, Meltem; Pritchard, Kathleen; Hawken, Steven; Dent, Susan (Frontiers in Cardiovascular Medicine, 2022)
Background: Trastuzumab has improved patient outcomes in HER2+ breast cancer (BC) but carries a risk of cardiotoxicity. Routine cardiac imaging is recommended for advanced breast cancer (aBC) patients during trastuzumab treatment despite a lack of evidence that this improves patient outcomes. This study was conducted to understand predictive factors for cardiac events and determine the impact of cardiovascular monitoring in aBC. Methods: This retrospective population-based cohort study included aBC patients treated with trastuzumab (all lines), in Ontario, Canada from 2007 to 2017. The overall cohort was divided into two groups; those who developed a cardiac event (CE) versus those who did not. Patients with pre-existing heart disease were excluded. Logistic regression was performed to identify patient characteristics associated with an increased risk of CE. Results: Of 2284 patients with HER2+ aBC treated with trastuzumab, 167 (7.3%) developed a CE. Median age at first dose of trastuzumab was 57 (IQR 49 – 66); 61 (IQR 51-70) for patients with a CE. Median number of cycles was 16 (IQR 7-32); 21 (IQR 8-45) for patients with a CE (p<0.01). 12 (0.5%) patients died of cardiac causes; all had a prior CE. Increased risk of CEs was associated with age >60 (OR 5.21, 95% CI 1.83 -14.84, p=0.05) and higher number cycles of trastuzumab (OR 1.01; 95% CI 1-101, p=0.028). Conclusions: This is the first population-based study to report on CEs and cardiac monitoring in HER2+ aBC patients during trastuzumab-based therapy. Older age and longer treatment with trastuzumab were associated with an increased risk of a CE.